Real-time imaging reveals local, transient vascular permeability and tumor cell intravasation stimulated by Tie2(Hi) macrophage-derived VEGFA - Harney, Allison S. (Cancer Discov, 2015)
Dissemination of tumor cells is an essential step in metastasis. Direct contact between a macrophage, Mena over-expressing tumor cell and endothelial cell [Tumor MicroEnvironment of Metastasis (TMEM)], correlates with metastasis in breast cancer patients. Here we show, using intravital high-resolution two-photon microscopy, that transient vascular permeability and tumor cell intravasation occur simultaneously and exclusively at TMEM. The hyperpermeable nature of tumor vasculature is described as spatially and temporally heterogeneous. Using real-time imaging we observed that vascular permeability is transient, restricted to TMEM, and required for tumor cell dissemination. VEGFA signaling from Tie2(Hi) TMEM macrophages causes local loss of vascular junctions, transient vascular permeability and tumor cell intravasation, demonstrating a role for TMEM within the primary mammary tumor. These data provide insight into the mechanism of tumor cell intravasation and vascular permeability in breast cancer, explaining the value of TMEM density as a predictor of distant metastatic recurrence in patients.